Factors influencing the level of insight and treatment attitude: a cross-sectional study of 141 elderly patients of major depression in Guangzhou, China - Yang, Hang; Chen, Jiao; Ye, Junrong; Zhou, Tingwei; Wang, Wen; Pan, Yuanxin; Wei, Yanheng; Lu, Xueling; Yuan, Lexin; Wu, Shengwei; Guo, Jianxiong; Xiao, Aixiang (Frontiers in Psychiatry, 2024)
Objective To explore the insight, treatment attitude, and related influencing factors of hospitalized elderly patients suffering from major depression.Methods A total of 141 hospitalized elderly patients with depression were selected as the research objects. Insight was evaluated by the total score of the Insight and Treatment Attitude questionnaire (ITAQ). The data collected included sociodemographic characteristics, psychiatric symptoms, delirium status, social functioning, social support, suicide risk, and cognitive function.The sample included 74.5% of female patients, and the mean age was 67.53 (sd=7.19) years. The influencing factors of inpatients with depression included alcohol consumption, length of hospitalization, admission types, and the main caregivers (P<0.05).The various factors were further analyzed by linear regression, revealing that the insight and treatment attitude of elderly depressed hospitalized patients were mainly related to the Mini-Mental State Examination (MMSE) (β= 0.225, 95% CI 0.055-0.395, P=0.01), dependent on a caregiver (β=-5.810, 95% CI -8.086~-3.535, P<0.001), the type of admission (involuntary admission) (β=-3.365, 95% CI -5.448~-1.283, P=0.002), Functional Activities Questionnaire (FAQ) (β=-0.156, 95% CI -0.303~-0.010, P=0.037), and length of stay (≤28 days) (β=2.272, 95% CI 0.055~-4.489, P=0.045).The level of insight was affected by cognitive function, involuntary admission, dependent on a caregiver, social function and length of stay. Future studies should focus on cognitive function recovery, observation of admission mode, and self-care ability in elderly patients with depression.